Modification of activated carbon using nitration followed by reduction for carbon dioxide capture - Shafeeyan, M.S.; Houshmand, A.; Arami-Niya, Arash; Razaghizadeh, H.; Daud, W.M.A.W. (WILEY-V C H VERLAG GMBH, 2015)
Activated carbon (AC) samples were modified using nitration followed by reduction to enhance their CO2adsorption capacities. Besides characterization of the samples, investigation of CO2 capture performance was conducted by CO2 isothermal adsorption, temperature-programmed (TP) CO2 adsorption, cyclic CO2adsorption-desorption, and dynamic CO2 adsorption tests. Almost all modified samples showed a rise in the amount of CO2 adsorbed when the comparison is made in unit surface area. On the other hand, some of the samples displayed a capacity superior to that of the parent material when compared in mass unit, especially at elevated temperatures. Despite ∼65% decrease in the surface area, TP-CO2 adsorption of the best samples exhibited increases of ∼10 and 70% in CO2 capture capacity at 30 and 100°C, respectively.